Indeterminacy in the small open economy Ramsey growth model - Mark Weder (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
This paper constructs a small open economy version of the two sector Benhabib-Farmer (1996) indeterminacy model. It can be shown that sunspot equilibria arise at significantly lower magnitude of increasing returns to scale than in the original dosed economy model. Furthermore, if a mix of externalities across sectors is admitted, indeterminacy can be obtained even with decreasing aggregate returns to scale.
urn:nbn:de:kobv:11-10056293
Keywords: F4; E32; 330